Impact of Nutritional Supplementation on Canine Dermatological Disorders - Andrea Marchegiani; Alessandro Fruganti; Andrea Spaterna; Elena Dalle Vedove; Benedetta Bachetti; Marcella Massimini; Francesco Di Pierro; Alessandra Gavazza; Matteo Cerquetella (Veterinary Sciences, 2020)
Nutritional supplements, also known as complementary feeds, are products administered with the aim of furnishing health benefits, regardless of nutritional needs. They have been used since ancient times in veterinary dermatology, and a number of studies have focused on investigating the health benefits of some ingredients found in commercially available complementary feed for dogs. The aim of this paper is to review the literature available on the use of nutritional supplementation for the management of canine skin diseases, critically appraising the clinical efficacy of such interventions and summarizing the current state of knowledge. This review highlights how these feeds can be considered useful in the management of dermatological disorders and outlines their beneficial effects in the prevention of dietary deficiencies and treatment of diseases, alone, or in addition to conventional pharmacological therapy. In recent years, nutritional supplements have found increasing potential application in veterinary medicine, and the scientific proofs of their beneficial effects are described in this review.